2022
DOI: 10.3847/1538-4357/ac731d
|View full text |Cite
|
Sign up to set email alerts
|

Mass-ratio Distribution of Binaries from the LAMOST-MRS Survey

Abstract: Binary evolution leads to the formation of important objects that are crucial for the development of astrophysics, but the statistical properties of binary populations are still poorly understood. The LAMOST-MRS has provided a large sample of stars to study the properties of binary populations, especially for the mass-ratio distributions and binary fractions. We have devised a peak amplitude ratio (PAR) approach to derive the mass ratio of a binary system based on results obtained from its spectrum. By computi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The LAMOST-MRS red and blue arms have respective wavelength ranges of 6300-6800 and 4950-5350 Å. We chose the spectra of the blue arm to detect triple-star candidates and measure their RVs, as they have more absorption lines (Li et al 2021(Li et al , 2022. Fernandez et al (2017) found that spectra with low signal-to-noise ratios (S/ Ns) posed a significant challenge for detecting ST candidates, and Li et al (2021) chose the blue arm spectra with S/Ns larger than 10.…”
Section: The Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The LAMOST-MRS red and blue arms have respective wavelength ranges of 6300-6800 and 4950-5350 Å. We chose the spectra of the blue arm to detect triple-star candidates and measure their RVs, as they have more absorption lines (Li et al 2021(Li et al , 2022. Fernandez et al (2017) found that spectra with low signal-to-noise ratios (S/ Ns) posed a significant challenge for detecting ST candidates, and Li et al (2021) chose the blue arm spectra with S/Ns larger than 10.…”
Section: The Datamentioning
confidence: 99%
“…Li et al (2021) used a cross-correlation function (CCF) and obtained 132 ST candidates from LAMOST-MRS DR7. We cross-matched Gaia DR3 with the STs and obtained their magnitudes in the Bp, G, and Rp bands (Gaia Collaboration et al 2018;Li et al 2022). Since the diameter of the LAMOST fiber is about 3″, we used the 3″ search cone to cross-match the spectrum of Gaia (Cui et al 2012).…”
Section: The Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of binaries including multiple stars is over half of all stellar systems (e.g., Duchêne & Kraus 2013;Moe & Di Stefano 2017;Li et al 2022), and it can be even up to 70% for massive stars (Sana et al 2012). The evolution of close binary stars can form X-ray binaries, pulsar binaries, type Ia supernovae, white dwarf/neutron star (NS)/stellar-mass black hole (BH) binaries, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of binary including multiple stars is over half of stellar systems (e.g. Duchêne & Kraus 2013;Moe & Di Stefano 2017;Li et al 2022) and it can be even up to 70% for massive stars (Sana et al 2012). The evolution of close binary stars can form X-ray binaries, pulsar binaries, type Ia supernovae, white dwarf/neutron star (NS)/stellar-mass black hole (BH) binaries, etc.…”
Section: Introductionmentioning
confidence: 99%